Globalization and Decriminalization of Cannabis in Nigeria: Lessons from the West - Nte, Ngboawaji Daniel; Lucas, Oluka Nduka; Joshua, Okotie Agbedia; Enokie, Bribena Kelvin (The Indonesian Journal of International Clinical Legal Education, 2020)
Contemporary global realities in the West have demonstrated the inestimable value of marijuana for recreational and medicinal purposes in addition to huge economic benefits. Consequently, a lot of European countries and the United States have accommodated this reality by methodically decriminalising or legalising the consumption of marijuana but rather regulated and institutionalised its production and distribution. The positive outcomes from the aforesaid arrangement cannot be over emphasised. Within the context of the above, Nigeria noted for one of the finest brands of marijuana must key into this vast economic and psycho-medical opportunities by modifying her laws and policies to harness these potentials as in the Western world. It is on this premise that this study affirms the economic benefits of marijuana or cannabis sativa (often known in our local slogan as â€œIndia hemp, igbo, we-we, ganja, weed, etcâ€). It is the view of this work that if Marijuana is methodically converted and cooperatively organised along other cash crops as export commodities, massive foreign exchange will be earned as part of the governmentâ€™s drive for a diversified economy. The study relied extensively on qualitative research design as its methodological component. Secondary sources of data were used in collection of relevant data or materials for the study, gleaned from extant literatures in the study area. In order to find the equilibrium point between decriminalisation of the management of marijuana and its political economic implications in Nigeria, while offering strategic solutions or policy recommendations.